Corporate standardization management and innovation - Jakobs, Kai 1957- (IGI Global, 2019)
"This book assesses the link between standards and efficiency in the business world. It also addresses the economic importance, global impacts, effective tools, and strategies employable across all levels of an organization"--
Keywords: Organizational effectiveness; Management; Information technology / Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior